Optimasi Formula Pasta Gigi Kombinasi Ekstrak Rimpang Temu Kunci dan Sereh dengan CMC-Na dan Carbomer sebagai Bahan Pengikat Menggunakan Metode Simplex Lattice Design - Hati, Anita Kumala; Dyahariesti, Niken; Yuswantina, Richa (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
Comercial toothpaste contain fluoride to prevent dental caries. The usage of fluoride in large quantities may cause irreversible enamel fluorosis, brittle bones, brittle teeth, premature aging, spontaneous abortion, and carcinogenic. Objective this experiment is knowing the extract concentration of finger roots and lemongrass which is equivalent to positive control and then performed optimization of toothpaste preparation formula with different concentrations of CMC-Na and carbomer with pH and viscosity parameters using the Simple Lattice Design method. The antibacterial test of lemongrass extract, finger roots and its combination with a concentration of 5% against Streptococcus mutans bacteria, showed the average diameter of the largest clear zone: finger roots extract was 11.167±0.288mm; combination of lemongrass extract:finger roots extract (1:2) was 10.83±0.288mm; combination of lemongrass extract: finger roots (2:1) was 10,067±1,006mm; lemongrass extract was 9.33±0.751mm; The combination of lemongrass extract:finger roots extract (1:1) was 9,133±0,321mm.. Post Hoc test results shows comparable to positive controls were 5% finger roots extracts, combination of lemongrass:finger roots 1:2 combination, and 2:1 combination. The optimum formula was obtained using the SLD method with a combination of 0.900% CMC-Na and 1,100% carbomer as a binding agent. The optimum pH formula of toothpaste was 7,613±0,076 and Viscosity 2,43,104cps±2571,640. The paired t-test pH obtained p-value 0.222 and the viscosity obtained p-value 0.934. The experimental results were not significantly different from the results predicted by the software simply latex design. The 5% finger roots extract can be developed into an herbal toothpaste with binding agent CMC-Na and a carbomer ratio of 0,9:1,1.